PENGARUH WAKTU TUNGGU PELAYANAN TERHADAP KEPUASAN PASIEN UNIT RAWAT JALAN DI RUMAH SAKIT - Resti Selviana; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
All statement items in the questionnaire for the service waiting time (X) and patient satisfaction (Y) variables were declared valid, because they had a significant correlation value with the total score (p < 0.05). In addition, the reliability test showed a Cronbach's Alpha value of 0.605 for variable X and 0.789 for variable Y. This indicates that the instrument used in this study is reliable and trustworthy. Based on the results of a simple linear regression analysis, a regression coefficient value of 0.331 was obtained with the value of service waiting time on patient satisfaction. The faster the waiting time, the higher the level of satisfaction felt by the patient. The Contribution of Waiting Time to Patient Satisfaction is Relatively Low The results of the analysis showed that the coefficient of determination (R²) value was 0.115, which means that service waiting time only explains 11.5% of the variation in patient satisfaction levels. The remaining 88.5% is explained by other factors not discussed in this study, such as the attitude of health workers, comfort of facilities, interpersonal communication, and clinical quality of service. The results of this study are consistent with various previous studies which show that waiting time is an important indicator in influencing patient perceptions and satisfaction with health services, especially in outpatient services.